Warthin-Like Papillary Thyroid Microcarcinoma With Coincidental Ipsilateral Warthin Tumor of the Parotid Gland Detected on 131I-SPECT/US and 18F-PET/US Fusion Imaging. (15th April 2023) - Werner, Anke; Freesmeyer, Martin; Bensch, Claudia; Eszlinger, Markus; Seifert, Philipp
Abstract: A 66-year-old woman was referred with an incidental finding of a bilateral papillary thyroid microcarcinoma after thyroidectomy. On the right side, a Warthin-like variant was observed. After radioiodine therapy, whole-body scan revealed an unclear iodine uptake on the right-sided neck. For further clarification, 131 I-SPECT/US and 18 F-PET/US fusion imaging were performed, unambiguously revealing iodine and glucose uptake within a hypoechoic lesion located in the parenchyma of the right parotid gland. Surgical excision confirmed a Warthin tumor ipsilateral to the Warthin-like variant of the papillary thyroid microcarcinoma. Because the extensive imaging, targeted minimal-invasive surgery was possible.